Peningkatan Pelayanan Data Keuangan Siswa Melalui Sistem Informasi Keuangan Monte Carmelo (SIMOKAR) dengan Metode Extreme Programming - Febriyanti Alwisye Wara; Henderikus Basilius Nong Muda; Lindiana Ermilinda; Conchita Junita Chandra; Theresia Wihelmina Mado; Maria Wihelmina Lodan (G-Tech: Jurnal Teknologi Terapan, 2024)
SMAK Santa Maria Monte Carmelo, a school under the Santa Maria Karmel Foundation in Wairklau-Maumere, currently still uses manual recording of student financial reports in a financial book. This system faces problems such as inaccurate financial reports and frequent data loss, which results in invalid financial reports. To overcome this problem, this research aims to develop an application that helps school treasurers record payments quickly and accurately. The application designed is the Monte Carmelo Financial Information System (SIMOKAR), using the Visual Basic programming language (VB.Net) and MySQL as data storage. During its development, this application adopted the Extreme Programming method to ensure effectiveness and accuracy in recording student financial payments. The research results show that this system has succeeded in implementing automatic and efficient payment recording in accordance with black box testing.The SIMOKAR application has a user satisfaction rating of 90%.